Case Report: Rehabilitation After Platelet-Rich Growth Factors’ Intra-Articular Injections for Knee Osteoarthritis: Two Case Reports of a Home-Based Protocol - Negrini, Francesco; De Lucia, Francesco; Negrini, Stefano; Tornese, Davide; Facchini, Francesca; Vecchio, Michele; de Girolamo, Laura (Frontiers in Pharmacology, 2021)
Knee osteoarthritis (KOA) is a chronic progressive disease that can cause pain, functional impairment, and ultimately disability. A novel and promising therapeutic approach to KOA is the so-called regenerative medicine, a set of procedures designed to harness tissue regenerative capacity and optimize functional recovery. Increasing evidence points out that platelet-rich plasma (PRP) intra-articular injections can decrease pain and improve functional abilities in KOA patients. In the present case reports, we analyze two patients who were treated with PRP injections coupled with a posttreatment home-based rehabilitation program. The two patients were selected to represent two different populations: patient 1 was an 85-year-old with severe impairment of functional abilities, while patient 2 was a younger (59 years old) and more active patient. The protocol consisted in a series of exercise to be performed at home, during the five days following PRP injection for two consecutive weeks (10 days in total). The exercises were designed to reduce the inflammation after the injection, enhance the proprioceptive control of the treated lower limb, and strengthen hip and knee flexors and extensors, mainly by isometric work. Results were evaluated at two time points: before and 2 months after the first PRP injection. The outcomes considered were as follows: visual analog scale for pain, EuroQol 5 dimensions questionnaire, Tegner Activity Scale for functioning, and Knee Injury and Osteoarthritis Outcome Score (KOOS). Both patients did not report any side effects from the treatment. Improvement in patient 1 was drastic at the two months follow-up as far as pain and functional abilities are concerned. Patient 2’s improvement was less evident, probably due to the higher starting point in both pain and functionality. Overall, the developed program seemed safe and was tolerated by the patients analyzed in the study, who performed it with good compliance.